2020
DOI: 10.1371/journal.pone.0225514
|View full text |Cite
|
Sign up to set email alerts
|

Chemical profiling of Curatella americana Linn leaves by UPLC-HRMS and its wound healing activity in mice

Abstract: Based on ethnopharmacological studies, a lot of plants, as well as its compounds, have been investigated for the potential use as wound healing agents. In Brazil, Curatella americana is traditionally used by local people to treat wounds, ulcers and inflammations. However, to the best of our knowledge, its traditional use in the treatment of wounds has not been validated by a scientific study. Here, some compounds, many of them flavonoids, were identified in the hydroethanolic extract from the leaves of C. amer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 62 publications
0
5
0
1
Order By: Relevance
“…These substances are generally absorbed well by the skin and modulate different stages of healing ( 26 ). Fujishima et al identified 13 compounds in a hydroethanolic extract from the leaves of C. americana , mainly quercetin, kaempferol, glucoside derivatives, catechin, and epicatechin, which could explain the excellent healing effect ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…These substances are generally absorbed well by the skin and modulate different stages of healing ( 26 ). Fujishima et al identified 13 compounds in a hydroethanolic extract from the leaves of C. americana , mainly quercetin, kaempferol, glucoside derivatives, catechin, and epicatechin, which could explain the excellent healing effect ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…exerted remarkable wound healing properties due to its active constituents. Leaves contain compounds known as wound-healing agents, mainly quercetin, kaempferol, glucosides, catechin, and epicatechin (Fujishima et al 2020).…”
Section: Wound Healing Potentials Of Various Plant Extractsmentioning
confidence: 99%
“…Nos estudos de Fujishima et al (2020), os pesquisadores encontraram inúmeros compostos através de análises por cromatografia líquida de alta eficiência (CLAE) americana coletadas no estado do Mato grosso, Brasil. Os pesquisadores obtiveram concentração de inibição com CI50 de 6,0 µg mL -1 e atividade máxima de 96,5% (25 µg mL -1 ), quando comparados ao BHT com CI50 18,3 µg mL -1 , e máxima atividade de 93,7% (500 µg mL -1 ), e para o ácido ascórbico com CI50 de 1,8 µL mL -1 e máxima atividade de 92,3 (10 µg mL -1 ).…”
Section: Sistemática E Fenologia De Curatella Americanaunclassified